Evolution Of India’s Nuclear Program - Sharma, Madhubala (International Journal of Psychosocial Rehabilitation, 2014)
The purpose of the research examines the evolution of India’s nuclear program as it developed from the 1940s by a small group of influential scientists and the current nuclear capabilities that they now posses. The Indian nuclear program continues to develop improved weapons technologies and economic development with the potential to proliferate nuclear material. India since 1947, in order to develop a comprehensive strategy that utilizes all the instruments of national power that will encourage India to become a responsible stakeholder among the nuclearized countries and demonstrate the responsibility that goes along with nuclear technology. India’s nuclear policy was also influenced by India’s international security condition as well as by domestic variables such as the vagaries of political change and the influence of bureaucratic elites. India aspired to be a nuclear state after 1962 conflict with China, particularity after China conducted its first nuclear test in 1964 The role of ‘the nuclear’ in global power status however is central to being recognized as a power to be reckoned with. Despite India’s nuclear tests in 1974 and 1998, such recognition had always eluded India. Since India was not a signatory to the NPT